A quasi-static test on a new type of masonry built of "I"-shaped closed-top hollow bricks. Issue 2 (3rd April 2017) - Wang, Teng; Zhou, Ming-ru; Ding, Yan-mei
Abstract: Seven small-scale models of "I"-shaped hollow-opened block masonry (five bonded with 1 mm loess mud, one with 1 mm cement paste and another with 5 mm mortar) were studied by pseudo-static test. The experimental result shows that, (1) the shear capacity and ductility of the specimens increase when the axial compression ratio is less than 0.7, decline when greater than 0.7. (2) the shear capacity is improved a lot by the interlock of hollow blocks which make full use of blocks' strength, with energy dissipation and seismic performance improved some as well. (3) the shear capacity of masonry is affected little by the thickness and strength of binding material, and so thin low strength mortar maybe more suitable for "I"-shaped hollow brick masonry, which can reduce cost and extend application range. The experimental investigation is another attempt to develop a new type of hollow brick masonry.